2012
DOI: 10.1111/j.1600-051x.2012.01915.x
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized comparative clinical study of two surgical procedures to improve root coverage with the acellular dermal matrix graft

Abstract: The proposed test technique is more suitable for root coverage procedures with ADMG, and the new parameter evaluated appears valuable for root coverage analysis. (Clinicaltrials.gov Identifier: NCT01175720).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
38
0
9

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(49 citation statements)
references
References 47 publications
(56 reference statements)
2
38
0
9
Order By: Relevance
“…At each treated tooth single sling mattress sutures were placed. They were removed 2 weeks afterwards in the case of the control group just as in Ayub et al [26], Koudale et al [27], and after 3 weeks in the case of the test group. A comparison of multiple gingival recession coverage procedures performed with the tunnel method using fascia lata Allograft as well as autogenous connective tissue graft indicates that similar clinical results were achieved at the end of a 6-month observation period.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At each treated tooth single sling mattress sutures were placed. They were removed 2 weeks afterwards in the case of the control group just as in Ayub et al [26], Koudale et al [27], and after 3 weeks in the case of the test group. A comparison of multiple gingival recession coverage procedures performed with the tunnel method using fascia lata Allograft as well as autogenous connective tissue graft indicates that similar clinical results were achieved at the end of a 6-month observation period.…”
Section: Discussionmentioning
confidence: 99%
“…Perhaps a different location for the allograft would have improved this result. This is because Ayub et al [26] showed that the positioning of the acellular dermal matrix allograft (ADMA) 1mm apically and the flap 1 mm coronally in relation to the CEJ results in statistically better widening of the keratinized gingiva than when the allograft is positioned at CEJ level.…”
Section: Discussionmentioning
confidence: 99%
“…In CG, this allograft was used with the technique developed by Barros et al 16 (Fig. 2B), whereas in the test group (TG), the technique proposes 1) a distance of 1 mm between the ADMG and CEJ to avoid its exposure and 2) a 1‐mm coronally advanced flap from the CEJ, compensating for primary soft tissue shrinkage 13 (Fig. 2C).…”
Section: Methodsmentioning
confidence: 99%
“…The clinical parameters evaluated were as follows: 1) probing depth (PD); 2) relative clinical attachment level (RCAL); 3) GR; 4) KT width; 5) thickness of KT (TKT); and 6) GRA. All clinical measurements were recorded by the same calibrated experienced periodontist (DBP) at the mid‐buccal point of teeth 13 scheduled for surgery at baseline and after 12 months with the aid of an acrylic stent to determine the exact measurement site. The examiner was masked to the procedures.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation